2020
DOI: 10.4314/ahs.v20i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of bacterial meningitis in Tunisian children, beyond neonatal age, using molecular methods: 2014-2017

Abstract: Background: Since the 1990s, the epidemiology of bacterial meningitis worldwide has changed thanks to vaccination. In Tunisia, the main causative pathogens were Streptococcus pneumoniae, Neisseria meningitidis and Haemophilus influenzae serotype b (Hib). Only Hib vaccination was available during our study period. Objectives: We performed a laboratory case report based-study of suspected bacterial meningitis in Northern Tunisia from January 2014 to June 2017. Methods: CSF samples obtained from child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…11 And Haddad-Boubaker et al reported that the most common bacterial meningitis agents were pneumococcus (69.84%), followed by meningococcus (28.57%) and Hib (1.59%), respectively, in Tunisian children between 2014 and 2017. 12 N. meningitidis was found to be the most common among bacterial agents in line with previous studies in our country conducted by Ceyhan et al 13 We think that this data available in our country is the result of routine vaccination against Hib and S. pneumoniae , although N. meningitidis is not in the routine immunization program. H. influenzae type b was not detected in our patients and only two cases of S. pneumoniae meningitis was found.…”
Section: Discussionsupporting
confidence: 90%
“…11 And Haddad-Boubaker et al reported that the most common bacterial meningitis agents were pneumococcus (69.84%), followed by meningococcus (28.57%) and Hib (1.59%), respectively, in Tunisian children between 2014 and 2017. 12 N. meningitidis was found to be the most common among bacterial agents in line with previous studies in our country conducted by Ceyhan et al 13 We think that this data available in our country is the result of routine vaccination against Hib and S. pneumoniae , although N. meningitidis is not in the routine immunization program. H. influenzae type b was not detected in our patients and only two cases of S. pneumoniae meningitis was found.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, bacterial co-infection cases due to Streptococcus pneumoniae and Haemophilus influenzae were the most prevalent and complicated. Noticeably, this study was achieved prior to the introduction of pneumococcal vaccine in April 2019 in Tunisia [35]. This vaccine is believed to substantially reduce the burden of pneumococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…There were more studies available on serogroup distribution from the EM region versus the NA region. Data were available from Iran (n = 2) [ 67 , 68 ], Kuwait (n = 1) [ 51 ], Qatar (n = 1) [ 69 ], Saudi Arabia (n = 6) [ 54 – 56 , 70 – 72 ], and Turkey (n = 8) [ 57 59 , 73 77 ], in the EM region (spanning 1987–2018), and from Egypt (n = 3) [ 61 , 78 , 79 ], Morocco (n = 6) [ 80 – 85 ], and Tunisia (n = 6) [ 64 , 86 – 90 ], in the NA region (spanning 1977–2019). Serogroups A, B and W were most frequently reported in the EM region, while B and C serogroups were most frequently reported in the NA region.…”
Section: Objective 2: Imd Epidemiologymentioning
confidence: 99%